2021
DOI: 10.1177/17588359211006957
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic mechanism-based pharmaceutical validation of therapeutics targeting MET receptor tyrosine kinase

Abstract: Aberrant expression and/or activation of the MET receptor tyrosine kinase is characterized by genomic recombination, gene amplification, activating mutation, alternative exon-splicing, increased transcription, and their different combinations. These dysregulations serve as oncogenic determinants contributing to cancerous initiation, progression, malignancy, and stemness. Moreover, integration of the MET pathway into the cellular signaling network as an addiction mechanism for survival has made this receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Yet, as amyloid-targeting drugs are new to the clinic and have much to prove in clinical settings, another class of AD drug is still in need. In this study, we identified another component of the amyloid-beta accumulation cycle, which are the MET signaling complex [19, 28], RAS, EGFR, PLCG and its downstream, the JNK-MAPK signaling. Hence, we propose that the MET complex, RAS, EGFR, PLCG and the JNK-MAPK signaling are new targets to inhibit the amyloid-accumulation cycle and AD intervention drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as amyloid-targeting drugs are new to the clinic and have much to prove in clinical settings, another class of AD drug is still in need. In this study, we identified another component of the amyloid-beta accumulation cycle, which are the MET signaling complex [19, 28], RAS, EGFR, PLCG and its downstream, the JNK-MAPK signaling. Hence, we propose that the MET complex, RAS, EGFR, PLCG and the JNK-MAPK signaling are new targets to inhibit the amyloid-accumulation cycle and AD intervention drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…MET (which stands for “mesenchymal-epithelial transition” or as an abbreviation for the mutagen N-methylnitrosoguanidine [ 150 ]) is a proto-oncogene and fusion gene discovered in the early 1980s [ 151 ] and found at locus 7q31 on human chromosome 7. It encodes the 170–180 kD, two-chain HGFR (hepatocyte growth factor receptor, or simply c-Met), a protein with transmembrane tyrosine-kinase function [ 152 ], and it is continuously being researched for its involvement in oncologic pathologies, predominantly of the lung and liver but also breast, ovarian, and GI cancers [ 153 ].…”
Section: C-met Inhibitorsmentioning
confidence: 99%
“…The dysregulation of the HGF/c-MET axis is closely related to malignant cellular transformation, invasion, and metastasis [ 239 ]. Abnormal MET pathway activation is characterized by MET exon 14-skipping mutations (METex14), MET overexpression, and MET amplification [ 240 ]. MET overexpression can be related to many factors, including the hypoxic environment and transcriptional upregulation of the receptor [ 241 ].…”
Section: Uncommon Mutations Of Nsclcmentioning
confidence: 99%